Bridging the Gap: Enhancing Open Fracture Care in Emergency Nursing: Menjembatani Kesenjangan: Meningkatkan Perawatan Fraktur Terbuka dalam Keperawatan Gawat Darurat - Ali A. Ahmed Al-Iedan; Mohamad A. Akber; Sundus Baqer Dawood; Ahmed Ibrahim Habib Alobaidi; Sajjad S. Issa; Husham Hussain Abdul Raaoof; Ahmed Ziarra Khalaf; Ali Malik Tiryag (Academia Open, 2024)
This study assesses the knowledge and practices of emergency department nurses regarding the care of open fractures, highlighting significant disparities in competence. Conducted across five hospitals, the descriptive, cross-sectional survey included 103 nurses, analyzed using SPSS with results expressed through frequencies, percentages, and Chi-squared tests. Findings reveal that 42.7% of nurses, predominantly females, lack adequate knowledge and care skills, whereas 57.3%, mostly males, are proficient. The study suggests an urgent need for focused training programs to standardize and elevate emergency care for open fractures, aiming to improve patient outcomes through enhanced nursing education. Highlights: Discrepancy in Knowledge: Significant variations in the knowledge and care practices for open fractures among emergency nurses, with nearly 43% lacking sufficient skills. Gender Differences: A notable gender-based disparity in knowledge, with a higher proficiency observed among male nurses compared to female nurses. Need for Training: The urgent requirement for specialized training programs to address gaps and improve overall patient care in emergency situations. Keywords: Open Fractures, Emergency Nursing, Knowledge Gap, Nurse Training, Patient Outcomes